Understanding hallmark event failure: a case study of a Swedish music festival. Issue 2 (5th June 2017) - Nordvall, Anders; Heldt, Tobias
Abstract : Purpose: Hallmark events can be very beneficial for host communities, not least due to their potential in attracting tourists. The Peace & Love music festival was the hallmark event of the Swedish city Borlänge. In 2013, the event organization declared bankruptcy and canceled the forthcoming festival. The purpose of this paper is to identify and discuss the factors that caused the failure of the 2013 Peace & Love festival. Design/methodology/approach: The case of the Peace & Love festival is analyzed using three data sources: interviews with the former members of the event organization; secondary data describing the Swedish festival industry; and festival visitors' perspectives represented by comments on social media. An organizational ecology perspective frames the analysis. Findings: The results of the study reveal that the failure of the event can be understood by a combination of three components: an organization in a vulnerable position, a strong new competitor entering the Swedish festival market, and uncertain visitors searching for the new place to be. Originality/value: Very few studies have researched event failure, although the subject is a recommended priority within the field of festival studies. This study presents a thorough examination of a hallmark event failure, which contributes to this area of knowledge and provides relevant information for organizations and host cities.